2006
DOI: 10.1007/s10853-006-1067-7
|View full text |Cite
|
Sign up to set email alerts
|

Activation energy determination for linear heating experiments: deviations due to neglecting the low temperature end of the temperature integral

Abstract: Model-free isoconversion methods which use approximations of the temperature integral are generally reliable methods for the calculation of activation energies of thermally activated reactions studied during linear heating. These methods generally neglect the temperature integral at the start of the linear heating, I (T o ). An analytical equation is derived which describes the deviations introduced by this approximation.It is shown that for most reactions encountered this assumption does not have a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(63 citation statements)
references
References 40 publications
(66 reference statements)
0
61
0
2
Order By: Relevance
“…This activation energy should be equal to the activation energy for S phase formation, which can be derived from experiments which measure the rate of S formation at different temperatures. For the present analysis, the activation energy is obtained from DSC experiments performed on a 2024-T351 alloy at different heating rates using iso-conversion methods [57,58]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This activation energy should be equal to the activation energy for S phase formation, which can be derived from experiments which measure the rate of S formation at different temperatures. For the present analysis, the activation energy is obtained from DSC experiments performed on a 2024-T351 alloy at different heating rates using iso-conversion methods [57,58]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is a reasonable assumption unless a process in question has low activation energy and becomes detectable at temperature close to the initial temperature. In such cases, neglecting the integral from 0 to T 0 may introduce some error to the estimated value of E. The issue has been studied by Starink [18], and some of the results of that study are shown in Fig. 2.2.…”
Section: Early Methodsmentioning
confidence: 99%
“…However, the above-mentioned ASTM E698 method which is called Kissinger method has a number of important limitations that should be understood, which arise from the underlying assumptions of the method [25,26]. The E a values obtained by using this method have the systematic error.…”
Section: Thermal Decomposition Kineticsmentioning
confidence: 99%